2017
DOI: 10.15517/ijds.v20i1.28952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microleakage by Gas Permeability and Marginal Adaptation of MTA and Biodentine™ Apical Plugs: In Vitro Study

Abstract: The endodontic treatment of teeth with incomplete development is always a complex task. Nowadays, biomaterials such as bioceramics offers promising clinical evidence that supports its use. However, the standardization of its use for apexification purpose still needs a deeper understanding of the materials’ behavior. The aim of this investigation was to evaluate the marginal adaptability and microleakage by gas permeability of MTA and Biodentine™ apical plugs in an in vitro model. Materials and methods: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Based on the MCT and OCT findings in this work, comparable outcomes were observed between Biodentine and MTA in the sealing ability, although to some extent, MTA demonstrated better performance than Biodentine. This was consistent with other studies [ 13 , 14 , 40 , 41 , 42 ], which found that MTA and Biodentine showed similar adaptation. MTA is expected to exhibit excellent adaptation is likely attributable to its expansion over time while it sets, which may reduce the gap within the cavity [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the MCT and OCT findings in this work, comparable outcomes were observed between Biodentine and MTA in the sealing ability, although to some extent, MTA demonstrated better performance than Biodentine. This was consistent with other studies [ 13 , 14 , 40 , 41 , 42 ], which found that MTA and Biodentine showed similar adaptation. MTA is expected to exhibit excellent adaptation is likely attributable to its expansion over time while it sets, which may reduce the gap within the cavity [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Yet, few studies have been conducted on Biodentine and TheraCal LC’s internal adaptation to the dentine of permanent teeth when utilized as an indirect pulp-capping material. Moreover, the findings have been inconsistent [ 9 , 13 , 14 ]. Additionally, a recent review concludes that these new materials require further investigation to better understand their cytotoxicity, bond strength, and dentin-bridge formation quality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our result matched with Brenes-valverde, et al (20) who compared the marginal adaptability and microleakage of MTA and Biodentine and statistically there was no significant difference between two materials. Also, with Dimitrova et al (17) in which the study involved comparing the adaptability potential of different calcium silicate based cements when used to treat large furcal perforations using SEM.…”
Section: Discussionsupporting
confidence: 91%